THE INFLUENCE OF INSTITUTIONAL OWNERSHIP AND PROFITABILITY ON COMPANY VALUE AT PT BISI INTERNASIONAL TBK - Nani Rusnaeni; Tri Wartono; Agus Supriatna (International Journal Management and Economic, 2024)
This research aims to determine the influence of Institutional Ownership and Profitability on Company Value at PT Bisi Internasional Tbk, both partially and simultaneously. The types of research used are quantitative and descriptive research. Data collection techniques were taken from the official website of PT Bisi Internasional Tbk during the 2011-2021 period. The data analysis method used in this research is multiple linear regression with SPSS 25.00. The results of hypothesis testing show that institutional ownership has a significant effect on company value, and profitability has a significant effect on company value. The results of simultaneous hypothesis testing show that Institutional Ownership and Profitability significantly affect Company Value, with a determination value of 71.3%. In comparison, the remaining 28.7% is influenced by other variables not examined in this research.